Genetic divergence among 22 strawberry (Fragaria x Ananassa Duch.) genotypes for bioactive compounds grown in northwest Himalayas - Lal, S; Singh, DB (SAARC Journal of Agriculture, 2016)
To analyze genetic divergence 22 strawberry genotypes (Fragaria x ananassa Duch.) were studied for six bioactive compounds traits at Central Institute of Temperate Horticulture (CITH), Srinagar, India. The maximum PCV and GCV were estimated for the total phenol content (23.78 and 23.87) followed by vitamin C (22.39 and 22.48). The heritability was highest for total phenols (99.61%) and DDPH (99.18). Genotypic correlation was of higher magnitude to the corresponding phenotypic ones. Titrable acidity exhibited highly negative association with vitamin C whereas total phenol content was showed significantly negative correlation with vitamin C but positive association with titrable acidity and total anthocyanin contents. DPPH and vitamin C negatively correlated, however DPPH exhibited highly positive and significant association with titrable acidity, total anthocyanin and total phenol contents. In path analysis, highest positive direct effect was exhibited by total phenol content (0.937) the highest negative direct effect by total flavonols (-0.055). The selection based on higher total phenols, titrable acidity and total anthocyanin contents will be beneficial for enhancing the total antioxidant potential attributes of strawberry germplam for commercial utilization and processing. The information also could be utilized to increase the nutritional value of different foods and diets in the prevention of chronic human diseases using strawberry genotypes having higher bioactive compounds. SAARC J. Agri., 14(1): 81-91 (2016)